MEMPOSISIKAN SANTRI DALAM PEMIKIRAN LIBERAL KEAGAMAAN DI INDONESIA - Saifuddin Saifuddin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
A religious reaction against modernity has opened our eyes, that an argumentation in the thought zone at the end enters the empiric zone. As a result is a horizontal conflct that meets a fundamentalist and radical islamic group facing a tolerant Islamic group and has liberal thought. Islamic liberalism indeed is not always identical with the western liberalism, but has a strong tradition in islamic world. The root of thought which becomes an argument in islamic world apparently is too close in santry those who get traditional and old-fashioned stereo type all this time. Pesantren has a strenght in overcoming the modernisation crash by the high of adaptive, tolerant and humanis character level, which can be chategorized as an islamic liberal. It is obviously that the thought character comes from the islamic teaching with rahmatan lil alamin character. This study shows the positive response shown by shalafih madrasah toward modernity, also the ability to assert self identity at once as pesantren’s heir in the middle of the crowded of consumtive culture. Inside the resource owned by shalafih madrasah, this study fids the root of religious liberalism thought which is represented by the deep religious science, passion and desire they have to develop sience. And a point should be highlighted here is not seeing a social problem from a black and white view.